IN SCHOOL CULTURE, IS THE NEEDY SPECIAL? (Fiep Bulletin - online, 2011)
The focus of this article is to talk about the Needy in a very special way, but mainly as a being that has rights and can discover as a person inside a school culture, which must comply with the inequalities so there is progress in achieving equality, aiming for a harmonious social life and healthy. We treat the Disabled as Especially Needy because, according to the history, terminology were changing due to new times, situations, and laws and with that being special with numerous needs was getting only one more stigma. However, he needs to be seen as unique and full of diversity, and not as a classification that only makes him feel increasingly different and labeled.